2020
DOI: 10.1364/oe.386752
|View full text |Cite
|
Sign up to set email alerts
|

Research on the new detection method of suppressing the skylight background based on the shearing interference and the phase modulation

Abstract: In order to effectively suppress the effect of the skylight background on the detection performance of the optical telescope and make it have the advantages of the all-time operation and the high star-magnitude detection, a new detection method based on the shearing interference and the phase modulation is proposed in this paper. This method utilizes the discrepancy of the spatial coherence between the target (smaller size) and the skylight background (larger size). By adjusting the shearing amount reasonably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The equation referenced as (20) is employed for the calculation of the atmospheric light denoted as A ∞ , where the mean pixel intensity within the designated set C at is utilized as an approximation of the total atmospheric light intensity. In this context, I r j , I g j , I b j represent the three component values of pixel j in the RGB color space, and N C at denotes the cardinality of the set C at .…”
Section: Identifying Pzci and A ∞mentioning
confidence: 99%
See 1 more Smart Citation
“…The equation referenced as (20) is employed for the calculation of the atmospheric light denoted as A ∞ , where the mean pixel intensity within the designated set C at is utilized as an approximation of the total atmospheric light intensity. In this context, I r j , I g j , I b j represent the three component values of pixel j in the RGB color space, and N C at denotes the cardinality of the set C at .…”
Section: Identifying Pzci and A ∞mentioning
confidence: 99%
“…Studies have shown that natural environments display distinct variations in energy levels based on different polarization states, spectra, and coherence characteristics between the sky background and objects within the scene [20,21]. This research presents a new method for predicting atmospheric light intensity by utilizing gradient data obtained from polarization images of natural scenes.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the above problems, the interference detection technique [ 7 , 8 , 9 , 10 ] has been proposed to improve the detection performance for finding dark stars. The interference detection technique uses the discrepancy of the far-field coherence between the target light and the skylight background to realize the separation of the two.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interference detection technique can be used alone to suppress the skylight background, or it can also be combined with traditional methods to achieve better suppression ability. Due to the shortcomings of the low interference contrast of target light and the low aperture utilization of the early interference detection technique based on electro-optic modulation devices [ 7 ], a shearing interference detection technique based on the double-grating structure [ 11 , 12 , 13 , 14 ] was proposed [ 10 ], which can significantly improve the interference contrast of target light and increase the aperture utilization. However, the published scheme of the shearing interference detection technique [ 10 ] uses a beam-shrinking telescope to reduce the interference fringe area and improve the fringe contrast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation